Esejizmi v romanu Vinka Ošlaka - Vollmaier Lubej, Janja (Jezik in slovstvo, 2016)
The present contribution examines essayism in the literary work of Vinko Ošlak. It presents the entwined essayistic thoughts in his three novels, in the autobiographical novel Človeka nikar and in the socially critical novels Hagar and Obletnica mature. The role and meaning of essayistic elements and essayistic excursions in the aforementioned literary works is analysed.
Keywords: Slovene literature; slovenska književnost; prose; proza; sodobni slovenski roman; esejizem; jezik; Language; narod; people; krščanstvo; Christianity; art; umetnost; literarne študije; Ošlak, Vinko: Človeka nikar; Ošlak, Vinko: Hagar; Ošlak, Vinko: Obletnica mature